Transcriptome and DNA methylation analysis of the goat pineal gland during puberty - Bochao Zhang; Genbao Zhu; Jianling Wu; Huihui Xie; Jiankun Cui; Wei Qian; Qing Yi; Fuqiang Pan; Fugui Fang; Yinghui Ling; Yunhai Zhang; Yunsheng Li; et al. (Scientific Reports)
Abstract Previous studies have confirmed that methylation regulates gene transcription in the hypothalamus-pituitary-gonadal axis during puberty initiation, but little is known about the regulation of DNA methylation on gene expression in the pineal gland. To screen pineal gland candidate genes related to the onset of goat puberty and regulated by genome methylation, we collected pineal glands from prepubertal and pubertal female goats, then, determined the DNA methylation profile by whole genome bisulfite sequencing and the transcriptome by RNA sequencing on Illumina HiSeqTM2500. We analyzed differentially expressed genes between the Pre group and Pub group using the DESeq2 software (version 1.20.0), and applied the Benjamini and Hochberg method for adjusting P-values. Genes with a P-value less than 0.05 and an absolute log2 fold change greater than 0 were considered differentially expressed genes. Results showed that there was no significant difference in the whole-genome methylation level of the pineal gland between prepubertal and pubertal goats, but the methylation pattern changed significantly, indicating that genomic DNA methylation of the pineal gland might play a role in regulating the initiation of goat puberty. Changes in DNA methylation patterns affected some pineal gland transcriptomes, while the transcriptional level of most genes remained unaffected by DNA methylation differences. Genes regulated by DNA methylation regulates genes primarily involved in metabolic processes, oxidative phosphorylation, and signaling pathways related to thermogenesis. Methylation significantly regulated the expression of genes such as ATP5F1D, CACNB2, and PTEN, while genes like LIN28B, GIP, OPN1SW, and DCC showed the most notable fold changes, which may indicate their involvement in the onset of puberty.